Seismic Vulnerability Index Mapping Based on PGA, GSS, and MMI Values in Pasar Ujung Kepahiang Village - Sapanur, Destika Meisy; Hadi, Arif ismul; Refrizon, Refrizon (Department of Physics Education, Universitas Mataram, 2024)
Pasar Ujung Village is located in Kepahiang District, which has the highest growth rate and population compared to other sub-districts in Kepahiang Regency, with a growth rate of 1.63% and a population of 53,066 thousand people. As one of the efforts to minimize the occurrence of damage due to earthquake disasters in Pasar Ujung Village, Kepahiang, it is necessary to map the seismic vulnerability index using the microtremor method. The research was conducted in Pasar Ujung Village, Kepahiang. Measurement points were placed at 28 points with a distance of approximately 200 m between points. Primary data used in this study came from microtremor surveys with A0 and f0 values. The results of the study are also included in the high-risk category for the social impact of earthquake disasters with an MMI value of more than 7. Based on the PGA map, it shows that the research location is quite prone to damage due to earthquakes, with a PGA value of > 564gal. Based on the PGA value obtained, the value is classified as instrumental intensity scale VI-VIII with shaking strength in the strong to very strong category. The magnitude of the earthquake, the depth of the source, and the distance of the earthquake source from the research location also contribute. The thickness of the surface sediment layer can be a consideration for people who will carry out development.